Temperate forests - Jennings, Terry J. (Oxford : Oxford University Press, 1986)
Discusses the temperate forests of the world, describing the kinds of trees, their life cycles, and how they are used by humans.
Includes bibliography: p. 44-45.
Keywords: Human geography -- Juvenile literature; Temperate forests -- Juvenile literature; Forest ecology -- Juvenile literature; Temperate forests; Forest ecology; Ecology